2002
DOI: 10.5194/angeo-20-257-2002
|View full text |Cite
|
Sign up to set email alerts
|

Confluence and redistribution of Atlantic water in the Nansen, Amundsen and Makarov basins

Abstract: Abstract. The waters in the Eurasian Basin are conditioned by the confluence of the boundary flow of warm, saline Fram

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
169
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(186 citation statements)
references
References 30 publications
(52 reference statements)
15
169
0
Order By: Relevance
“…This is certainly not true. Both eddies, likely caused by baroclinic instability at the confluence of the two branches (Schauer et al, 2002a), as well as interleaving and consecutive doublediffusive fluxes (Rudels et al, 1999) have been shown to exchange water between the branches and to reduce the respective extremes of temperature and salinity. Since Barents Sea water has been cooled to less than 0 • C when it encounters the Fram Strait branch in the northern Kara Sea our approach might overestimate the heat transport divergence if it captures cold Barents Sea water in the outflow part of the assumed stream tube instead of warmer Fram Strait Water which is returning further west.…”
Section: Discussion Of Inherent Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is certainly not true. Both eddies, likely caused by baroclinic instability at the confluence of the two branches (Schauer et al, 2002a), as well as interleaving and consecutive doublediffusive fluxes (Rudels et al, 1999) have been shown to exchange water between the branches and to reduce the respective extremes of temperature and salinity. Since Barents Sea water has been cooled to less than 0 • C when it encounters the Fram Strait branch in the northern Kara Sea our approach might overestimate the heat transport divergence if it captures cold Barents Sea water in the outflow part of the assumed stream tube instead of warmer Fram Strait Water which is returning further west.…”
Section: Discussion Of Inherent Uncertaintiesmentioning
confidence: 99%
“…There is no indication that the Barents Sea branch that enters the central Arctic Ocean through the St. Anna Trough crosses any of the WSC-derived loops. Rudels et al (1994) and Schauer et al (2002a) showed that the Barents Sea water displaces the Fram Strait branch off the slope at the confluence of the two branches in the northern Kara Sea and that further downstream the two branches run parallel with the Barents sea branch at the slope side and the Fram Strait branch flowing at the basin side (Fig. 1).…”
Section: A Stream Tube Concept For the West Spitsbergen Currentmentioning
confidence: 99%
“…[3] Several papers have proposed schemes for the Atlantic water pathway [e.g., Rudels et al, 1994;Schauer et al, 2002] that cyclonically follow the shelf slope and midocean ridge margins of the major basins, but many important features are uncertain (Figure 1). One of the Atlantic water gyres is in the Amundsen Basin (AB) with flow along the Russian continental slope and returning towards Greenland along the AB flank of the Lomonosov Ridge (LR).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature and heat content in the AW layer is influenced by both the warm Fram Strait and the cold BSO AW branches, the latter of which joins the former mainly through the St. Anna Trough (Schauer et al, 2002). Using passive tracers we can 15 obtain the spatial distribution of the two water sources (Fig.…”
Section: Atlantic Water (A) Heat Content and Water Mass Sourcesmentioning
confidence: 99%
“…The warmer Fram Strait branch and colder BSO branch converge north of the Kara Sea (Schauer et al, 2002;Karcher and Oberhuber, 2002;Maslowski et al, 2004) and con-5 tinue eastward along the Eurasian slope. After passing the Laptev Sea slope, the boundary current bifurcates into one branch following the Lomonosov Ridge and another following the continental slope (Woodgate et al, 2001).…”
Section: Model Setupmentioning
confidence: 99%